Validation of Interferon Induced IFIT Genes in Host Antiviral Defence Against BTV16 Infection : An Initial Report - J, Manimegalai; Prasad, Minakshi; Brar, Basanti; Ikbal,; Gandham, Ravi Kumar; Lambe, Upendra P; Ranjan, Koushlesh; Misri , Jyoti (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Whole blood samples were collected from healthy sheep and goat, Peripheral blood mononuclear cells (PBMC) isolation was done from whole blood of both the species and cultured in six well plates using RPMI-1640 media in the presence of 5% CO2 at 37 0C. Bluetongue (virus BTV)-16 infection was given in PBMCs of both the species at 0 h and representative samples were collected at 24, 48 and 72 h. Total RNA was extracted and cDNA was obtained by reverse transcription. All the four differentially expressed genes (IFITs genes) were validated using quantitative real time PCR and the target gene expression was studied in fold change at 24, 48 and 72 h post infection of sheep and goat PBMCs against BTV-16 infection along with mock infected cells as control. Up regulation in target gene expression was found in virus infected PBMCs of both the species at all the time intervals than control PBMCs indicates the antiviral host protective response of those DEGs against BTV-16 infection. NS1 gene expression of BTV16 in sheep and goat PBMCs at different time interval were also determined which showed significant variation in both species.